Pengaruh Gaya Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru Sekolah Menengah Atas Negeri 4 Bone - Syukur Syukur; Sitti Hasbiah; Uhud Darmawan Natsir (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This study aims to determine the effect of the principal's leadership style on the performance of teachers at the State Senior High School 4 Bone. This research variable consists of leadership style and performance. This type of research is quantitative associative. The population was 38 teachers at State Senior High School 4 Bone. The sampling technique used was saturated sampling with a sample size of 38 respondents, namely the entire population. The data collection technique was carried out by distributing questionnaires to employees. Data analysis techniques using simple regression with the help of SPSS software version 25. The results of this study indicate that the principal's leadership style has a positive and significant effect partially on teacher performance at State Senior High School 4 Bone.